2019
DOI: 10.1177/0363546519835491
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tendon Delamination on Rotator Cuff Healing

Abstract: Background: While patient age, tear size, and muscle fatty infiltration are factors known to affect the rate of tendon healing after rotator cuff repair, the effect of tendon delamination is less known. Purpose: To assess the effect of tendon delamination on rotator cuff healing after arthroscopic single-row (SR) repair. Study Design: Cohort study; Level of evidence, 3. Methods: Consecutive patients (N = 117) with chronic full-thickness rotator cuff tears underwent arthroscopic SR repair with the tension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 39 publications
1
35
0
1
Order By: Relevance
“…With further research on the anatomical structure of the footprint area of the rotator cuff, it was found that there are two different layers of tissue structure on the end of the footprint area of the rotator cuff and that the two layers of tissue structure have different tension. The rotator cuff tear often leads to a change in stratification, and each layer of structure has a different degree of retraction [12,17]. Therefore, to restore the original anatomical structure of the rotator cuff in the footprint area, arthroscopic DR is increasingly used in clinical practice.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…With further research on the anatomical structure of the footprint area of the rotator cuff, it was found that there are two different layers of tissue structure on the end of the footprint area of the rotator cuff and that the two layers of tissue structure have different tension. The rotator cuff tear often leads to a change in stratification, and each layer of structure has a different degree of retraction [12,17]. Therefore, to restore the original anatomical structure of the rotator cuff in the footprint area, arthroscopic DR is increasingly used in clinical practice.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%
“…The rotator cuff has a structure comprising 5 histologically different layers, and delamination tends to develop between the 2nd and 3rd layers with different ber distributions [30,31]. Delamination is one of the risk factors for postoperative retear after rotator cuff repair and healing; thus, repair with special attention to the possible presence and state of delamination is considered important [3][4][5]. For the delamination repair, methods suturing the super cial and deep layers en bloc [32,33], individually suturing the super cial and deep layers, and suturing only super cial layer [8,14,34,35] have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The delamination of the rotator cuff has been described as a horizontal lesion between the super cial and deep layers [1,2]. Delamination is observed in 36-82% of rotator cuff tear cases [3][4][5][6][7][8][9] and its presence is considered a risk factor for postoperative retear after rotator cuff repair [4]. Double-row double layer xation was reported as a repair method of the stump of delaminated rotator cuff tears, but a high incidence of retear in large and massive rotator cuff tear cases has been known [2,10], and optimal xation method for rotator cuff stump with delamination has yet been under debate.…”
Section: Introductionmentioning
confidence: 99%
“…5 Additionally, there is concern that rotator cuff tendon delamination worsens as tear size increases and that delamination is associated with greater risk of repair failure when a single-row technique is used. 6 Placement of this anterolateral anchor is an important final step in the repair of massive tears according to the anatomic vector repair technique.…”
Section: Discussionmentioning
confidence: 99%